1994
DOI: 10.1159/000147555
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Analysis of the Development of the Human Temporomandibular Joint and Masticatory Muscle

Abstract: The calcification levels of the mandible and the temporal bone of human fetuses, which ranged from 12 to 32 weeks of gestation, were systematically investigated with a soft X-ray analyzer linked to an image analyzer. The profile of the condylar process (head) revealed high levels of calcification, in contrast to that in the mandibular fossa of the temporal bone. The basal portion of the condylar process and the mandibular notch exhibited moderate calcification from 12 weeks of gestation. The weight and the cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
1
4
0
2
Order By: Relevance
“…From 28 weeks, masticatory muscles were associated with the increased radiographic density of the TMJ during formation of the human mandible (Sato et al, 1994). In our results, radiographic density level at the MS of the mandible gradually increased from 16 weeks to 28 weeks.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…From 28 weeks, masticatory muscles were associated with the increased radiographic density of the TMJ during formation of the human mandible (Sato et al, 1994). In our results, radiographic density level at the MS of the mandible gradually increased from 16 weeks to 28 weeks.…”
Section: Discussionsupporting
confidence: 61%
“…Condensed cellular mesenchyme of the condylar blastema is closely associated with the perichondral fibrous tissue of Meckel's cartilage (Lee et al, 2001). The function and development of masticatory muscles affect the development of the human mandible (Bresin et al, 1999;Kiliaridis and Katsaros, 1998;Sato et al, 1994). Hyoid muscles (digastric and geniohyoid muscles) insert into the periosteum and endosteum connective tissue of immature and mature bone in the medial region of the mandible.…”
mentioning
confidence: 99%
“…remained unanswered. It was suggested that it may depend on the early mouth opening movement, primarily induced by tongue musculature which matured quite early in orofacial structures (Bresin et al, 1999;Kang et al, 1992;Kiliaridis and Katsaros, 1998;Lee et al, 1990;Lightfoot and German 1998;Ogutcen-Toller and Juniper, 1993;Radlanski et al, 1999;Robertson and Bankier 1999;Sato et al, 1994). It was also reported that it may be influenced by mandibular movement in the human embryo beginning around week 8 of fertilization, when the temporomandibular joint is yet to be formed (Hall 1982a,b;Kjaer, 1997;Ouchi et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In early stages (up to 53 mm CRL) movement of the mandibular structures hinged at the most distal part of Meckel's cartilage seems to be obvious. Active movement can be expected in this region as soon as muscles have developed (36). As soon as a protrusion has formed at the distal end of the mandibular bone a mutual interaction between temporal and mandibular tissue can be assumed to shape the outlines of the glenoid fossa and the condylar process, as well as the other joint tissues involved.…”
Section: Discussionmentioning
confidence: 99%